(untitled) (Pedagogy of Higher and Secondary Education, 2004)
The article is devoted to research of the problem of revealing of the gifted and talented pupils. The author analysesbriefly the interpretations of the conception of “giftedness”, based not only on intellectual aptitudes, but on a number of otherimportant personality characteristics.